The Cytoarchitecture of the Tectal-Related Pallium of Squirrelfish, Holocentrus sp. - Demski, Leo S.; Beaver, Joel A. (Frontiers in Neuroanatomy, 2022)
The squirrelfish, which live in visually complex coral reefs, have very large eyes and a special dual-system “day and night vision” retina. They also have atypical expansions of brain areas involved in processing visual information. The midbrain tectum sends information via diencephalic relay to two enlarged dorsal telencephalic regions. The latter include a superficial dorsal/lateral “cortex-like area” of small to medium-sized cells [area dorsalis telencephali, pars lateralis-dorsal region (dorsal segment); Dld1] which projects to an underlying dorsocentral region of relatively large cells (the area dorsalis telencephali, pars centralis-dorsal region; Dcd) which in turn reconnects with the tectum. Additionally, the cerebellum is also involved in this pathway. The hypertrophied pallial regions, termed the tectal-related pallium (TRP), most likely exert major influences on a variety of visually-related sensorimotor systems. This research aimed at better establishing the cellular structures and possible connections within the TRP. Nissl and rapid Golgi staining, biotinylated dextran amine tracing and cell-filling, and electron microscopy were used in this study. For gross observation of the pallial areas and plotting of the study sites, a mini-atlas of transverse and horizontal sections was constructed. This research better documented the known cellular elements of the TRP and defined two novel cell types. Species differences in the TRP may be related to possible differences in behavior and ecology.